EFFECT OF DHATRIYARISHTA IN THE MANAGEMENT OF PANDUROGA (IRON DEFICIENCY ANAEMIA) - Dave, Urvi; Thakar, Anup (International Journal of Ayurveda and Pharma Research, 2015)
Iron Deficiency Anaemia (IDA) is the most common type of Anaemia overall, and is caused when the dietary intake or absorption of Iron is insufficient. Iron is essential portion of Hemoglobin and low Iron levels results in decreased incorporation of Hemoglobin into Red Blood Cells and thus Anemia develop. Classically it can be compared with the Panduroga by their similar signs and symptoms. Acharya Charaka has described Panduroga under Rasa Kshayajanya Vyadhi, which may cause malnourishment and deficiency of next Dhatu Rakta (Blood). Here 28 patients were selected in the study and randomly divided into two groups. Group A received Dhariyarista, Group B received Control drug Ferrous sulphate. At the end of 45 days symptomatic improvement and increase in Hb% in Group A was noticed compared to Group B. No significant therapy is there for chronic Anaemias in Modern science, which are often due to metabolic defect, so an attempt has been made to evaluate the efficacy of Dhariyaristha on Iron Deficiency Anemia. Reported that this drug has useful role in preventing Iron deficiency Anemia due to metabolic defect.